Far-Infrared Therapy Promotes Nerve Repair following End-to-End Neurorrhaphy in Rat Models of Sciatic Nerve Injury. (3rd February 2015) - Chen, Tai-Yuan; Yang, Yi-Chin; Sha, Ya-Na; Chou, Jiun-Rou; Liu, Bai-Shuan
Abstract : This study employed a rat model of sciatic nerve injury to investigate the effects of postoperative low-power far-infrared (FIR) radiation therapy on nerve repair following end-to-end neurorrhaphy. The rat models were divided into the following 3 groups: (1) nerve injury without FIR biostimulation (NI/sham group); (2) nerve injury with FIR biostimulation (NI/FIR group); and (3) noninjured controls (normal group). Walking-track analysis results showed that the NI/FIR group exhibited significantly higher sciatic functional indices at 8 weeks after surgery (P < 0.05 ) compared with the NI/sham group. The decreased expression of CD4 and CD8 in the NI/FIR group indicated that FIR irradiation modulated the inflammatory process during recovery. Compared with the NI/sham group, the NI/FIR group exhibited a significant reduction in muscle atrophy (P < 0.05 ). Furthermore, histomorphometric assessment indicated that the nerves regenerated more rapidly in the NI/FIR group than in the NI/sham group; furthermore, the NI/FIR group regenerated neural tissue over a larger area, as well as nerve fibers of greater diameter and with thicker myelin sheaths. Functional recovery, inflammatory response, muscular reinnervation, and histomorphometric assessment all indicated that FIR radiation therapy can accelerate nerve repair following end-to-end neurorrhaphy of the sciatic nerve.